SEVERAL PURPOSES WITH ONE COURSE – THE CHALLENGE OF TEACHING TERMINOLOGY AS PART OF A PRACTICAL TRANSLATOR TRAINING PROGRAMME - Richter, Borka (Neofilolog, 2018)
Within the field of Translation Studies, terminology plays an important role, as does the study of Terminology. This paper investigates the possibilities available within the constraints of a single course aiming to achieve multiple aims. A brief overview of how terminology is studied is followed by a presentation of the context, looking at the position of the course in relation to other courses in the same programme, and at the broader context of Translation Studies in Europe. The case study is of a Terminology course, as part of a post-graduate, two-semester, part-time programme in Translation, at Kodolányi János University of Applied Sciences in Hungary. The question of why terminology has a course to itself is likewise placed in the context of Terminology Studies and theoretical issues related to what terminology is. Finally, the course is also placed within the context of training students to become professionals in translation and related fields.